EFFECT OF FOLIAR FEEDING WITH LIQUID NITROGEN FERTILIZERS ON THE GROWTH AND DEVELOPMENT OF WINTER WHEAT - Davronov Qakhranomjon Anvarjonovich; Saminov Avazbek Alimardon oglu (Web of Journals Publishing, 2025)
In this article winter wheat liquid nitrogen fertilizer Application of standards and deadlines of winter wheat Study the effects on growth and development It is a pressing issue to continue scientific research on improving the agrotechnology of winter wheat cultivation in order to increase the yield and quality of wheat grain and to obtain high-quality grain crops. Therefore, the aim of winter wheat care is to achieve high-quality grain crops by improving the agrotechnology of winter wheat cultivation and improving the quality of winter wheat grain by using liquid nitrogen fertilizers.
Keywords: Liquid nitrogen fertilizer, winter wheat, field area, leaf, application, rate, period, option, height, number of joints, ear, yield.